2008
DOI: 10.1007/s00412-008-0187-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA bridging of yeast chromosomes VIII leads to near-reciprocal translocation and loss of heterozygosity with minor cellular defects

Abstract: Loss of heterozygosity (LOH) of tumor suppressor genes in somatic cells is a major process leading to several types of cancer; however, its underlying molecular mechanism is still poorly understood. In the present work, we demonstrate that a linear DNA molecule bridging two homologous chromosomes in diploid yeast cells via homologous recombination produce LOH-generating regions of hemizygosity by deletion. The result is a near-reciprocal translocation mutant that is characterized by slight cell cycle defects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…In the same strain, we also found the overexpression of the caspase YCA1 gene and of GSH1, which is also involved in apoptosis and cellular response to oxidative stress. Interestingly, previous authors (Tosato et al 2009;D. Nikitin personal communication) have revealed that VMR1 upregulation was also present in other homologous and heterologous BIT translocants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the same strain, we also found the overexpression of the caspase YCA1 gene and of GSH1, which is also involved in apoptosis and cellular response to oxidative stress. Interestingly, previous authors (Tosato et al 2009;D. Nikitin personal communication) have revealed that VMR1 upregulation was also present in other homologous and heterologous BIT translocants.…”
Section: Resultsmentioning
confidence: 99%
“…The names of the analyzed genes are reported in Figure 8 and in Table S3. As in previous expression analyses of BIT translocants, HSC82 was chosen as a constitutive control gene (Nikitin et al 2008;Tosato et al 2009). For all the genes analyzed, an expression level higher than twice, or equal to or lower than half, the expression level of the control strain San1, was considered as a significant up-or downregulation of transcription, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations